Jenis-jenis Famili Cyperaceae Di KHDTK ULM Mandiangin Kabupaten Banjar - Aulia Irmayanti; Bunda Halang (Program of Biology Education, Universitas Lambung Mangkurat, 2026)
The Cyperaceae family was a group of sedge plants with a herbaceous habit, generally had triangular stems, and compound flowers. Until that time, data regarding the species of Cyperaceae family in KHDTK ULM Mandiangin, Banjar Regency, were not available. This research aimed to describe the types of Cyperaceae found in the area. The method used was descriptive with purposive sampling technique through exploratory sampling. The results of the study showed that nine species of the Cyperaceae family were identified, namely Cyperus compressus, C. eragrostis, C. haspan, C. polystachyos, C. squarrosus, Fimbristylis dichotoma, Kyllinga brevifolia, K. nemoralis, and Scleria sumatrensis.